Real-world data on PD-1 inhibitor therapy in metastatic melanoma. (3rd July 2019) - Arheden, Anna; Skalenius, Joanna; Bjursten, Sara; Stierner, Ulrika; Ny, Lars; Levin, Max; Jespersen, Henrik
Abstract: Introduction: Phase III studies of PD-1 inhibitors have demonstrated remarkable improvements in the survival of patients with metastatic melanoma (MM). If these results are generalizable to an unselected patient population treated in clinical routine is unknown. This study aimed to investigate and describe clinical efficacy and safety of PD-1 inhibitors in patients with MM treated in routine clinical practice. Material and methods: A retrospective descriptive study of patients with metastatic or inoperable cutaneous melanoma treated with PD-1 inhibitors at a single institution (Department of Oncology, Sahlgrenska University Hospital) from 1 September 2015 to 31 August 2017. Data were obtained from medical records. Results: A total of 116 patients were included in the analyses. The overall survival (OS) at 12-month follow-up was 70.2% and the median OS was 27.9 months. Patients with BRAF mutated tumors had increased OS, whereas ECOG PS ≥2, LDH > ULN and presence or history of brain metastases (stage M1d) were associated with impaired survival. Immune-related AEs of any grade occurred in 64 (55.2%) patients and 15 (12.9%) patients experienced immune-related AEs of grades 3 and 4. Notably, rheumatic adverse events occurred at a higher rate (15.5%) than previously reported. The occurrence of immune-related AEs was associated with a benefit in OS, while the severity of immune-related AEs did not affect survival, nor did the use of systemic corticosteroids. Conclusions: The efficacy and safety of PD1 inhibitors in routine clinical practice appear comparable to that described in clinical trials.